Phytochemicals profiling, in vitro and in vivo antidiabetic activity, and in silico studies on Ajuga iva (L.) Schreb.: A comprehensive approach - Abomughaid Mosleh M.; El-Shibani Fatma A. A.; Abdulkarim Abdulnaser Kh.; Abouzied Amr S.; Sulaiman Ghassan M.; Abomughayedh Ali M.; Abdulsayid Munira M. F.; Albukhaty Salim; Elrmali Naema; Al-Saffar Ali Z.; El-khawaga Hend A.; Mohammed Hamdoon A. (Open Chemistry, 2024)
Ajuga iva (L.) Schreb. is a well-known antidiabetic medicinal plant used for several traditional medicine aspects in different areas of the world, including Libya. This study includes phytochemical analysis, antidiabetic evaluation, and in silico studies of the plant, A. iva, growing in Libya. The constituents of the plant were profiled using LC-MS/MS-QTOF analysis, and a total of 28 compounds were tentatively identified, including engeletin, pyrocatechol, eriodyctiol-7-hexoside, and 3,4-dihydroxybenzaldehyde, as major constituents. In addition, the steroidal compounds, i.e., 20-hydroxyecdysone, 24-dehydroprecyasterone, makisterone A, and ajugasterone D, which are considered chemomarkers for the plant, were also annotated by LC-MS analysis. The plant extract induced inhibition of α-amylase and α-glucosidase enzymes at IC50 values of 0.18 and 0.12 mg/mL, compared to the IC50 of the standard acarbose at 0.11 and 0.09 mg/mL, respectively. Fasting blood glucose (FBG, 360.7 mg/dL) levels were significantly reduced by the treatment of streptozotocin (STZ)-diabetic animals with 400 mg/kg (140.5 mg/dl) and 500 mg/kg (112.3 mg/dL) doses of the plant extract. The plant extract also induced a significant (p < 0.01) increase in insulin serum level compared to the untreated diabetic rats; however, the higher dose of the plant induced similar insulin induction compared to glibenclamide. Histopathological examination of the pancreatic and liver tissues indicated that A. iva extract induced regeneration in the islets of Langerhans and liver cells compared to the untreated diabetic rats. Docking analysis demonstrated that eriodyctiol-7-hexoside, echinacoside, and 2″-galloylhyperin showed the lowest binding energies to the target sites of α-amylase and α-glucosidase enzymes, indicating their potential role in A. iva antidiabetic bioactivities. The results support the recorded traditional bioactivity of A. iva as an antidiabetic herb, whereas its contents of polyphenols play a major role in the plant’s antidiabetic effect.